Multiple Epithelioid Hemangiomas with Orbital Involvement - Branislava Miličić; Tomaž Velnar; Rado Pregelj; Clara Limbaeck-Stokin (Case Reports in Pathology)
Epithelioid hemangioma, also known as angiolymphoid hyperplasia with eosinophilia, is a cutaneous angioproliferative lesion that follows a benign clinical course. It is most frequently localized in the skin of the head and neck region; although it may sometimes arise deeper in soft tissues, orbital involvement is rare. Here we describe a patient who developed multiple epithelioid hemangiomas, including an intraorbital lesion. The histopathological parallels with other reactive and neoplastic lesions as well as therapeutic options are discussed.